2011
DOI: 10.1089/dna.2010.1179
|View full text |Cite
|
Sign up to set email alerts
|

Association of Signal Transducer and Activator of Transcription 3 Gene Polymorphisms with Cervical Cancer in Chinese Women

Abstract: Signal transducer and activator of transcription (STAT) plays an important role in regulating cell proliferation, differentiation, and apoptosis. Previous studies revealed that abnormal expression/activation of STAT family members were present in a large group of human malignant tumors. In the present study, using polymerase chain reaction (PCR)-restriction fragment length polymorphism, DNA sequencing, and Taqman probe real-time PCR techniques, we analyzed two single-nucleotide polymorphisms (SNPs) in the STAT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…Moreover, polymorphisms in the IL21-JAK-STAT signaling pathway are associated with cardiovascular disease [26], breast cancer [27], renal cell carcinoma [28] and chronic myelogenous leukemia [29]. IL-21 gene polymorphisms such as rs12508721 T/C and rs2221903 A/G are also recognized as risk factors for HBV-related HCC and chronic HBV infections [30].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, polymorphisms in the IL21-JAK-STAT signaling pathway are associated with cardiovascular disease [26], breast cancer [27], renal cell carcinoma [28] and chronic myelogenous leukemia [29]. IL-21 gene polymorphisms such as rs12508721 T/C and rs2221903 A/G are also recognized as risk factors for HBV-related HCC and chronic HBV infections [30].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Moreover, the association between single nucleotide polymorphisms (SNPs) of STAT3 and susceptibility to carcinogenesis has been confirmed. 22,23 Additionally, it has been recognized that increased expression of STAT3 correlates with tumor progression and invasiveness; however, the causal mechanism of this molecular alteration and its prognostic value still remain unclear. Up to now, there have been few studies focused on SNPs in the STAT3 gene and their effect on gene expression, as well as their correlation with NSCLC risk, especially in the European population.…”
mentioning
confidence: 99%
“…Recently, increasing evidence shows that polymorphisms of the STAT3 gene are associated with various diseases [21, 3133]. In a large German cohort study, a significant association was observed between the minor allele of STAT3 rs744166 and Crohn's disease (OR = 0.83, 95% CI = 0.688–0.998, and P = 0.04) [31].…”
Section: Discussionmentioning
confidence: 99%